2012
DOI: 10.1152/ajpheart.00453.2011
|View full text |Cite
|
Sign up to set email alerts
|

Short-term magnesium deficiency upregulates ceramide synthase in cardiovascular tissues and cells: cross-talk among cytokines, Mg2+, NF-κB, and de novo ceramide

Abstract: BT. Short-term magnesium deficiency upregulates ceramide synthase in cardiovascular tissues and cells: crosstalk among cytokines, Mg 2ϩ , NF-B, and de novo ceramide. Am J Physiol Heart Circ Physiol 302: H319 -H332, 2012. First published October 7, 2011 doi:10.1152/ajpheart.00453.2011.-The present study tested the hypotheses that 1) short-term dietary deficiency (MgD) of magnesium (21 days) would result in the upregulation of ceramide synthase (CS) in left ventricular (LV), right ventricular, atrial, and aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 73 publications
0
46
0
Order By: Relevance
“…These factors will sustain and perpetuate the atherogenic process forming, eventually, fibrous tissue and further enlargement of the lesion, which will overlie a core of lipid resulting in plaques and necrotic tissue. Using rabbits and rats, we have demonstrated that feeding the animals diets low in Mg (similar to the levels found in American diets) results in all of the hallmarks of atherosclerosis, i.e., inflammation followed by release of hydrolytic enzymes, release of cytokines, release of chemokines and growth factors involved in the early stages of the atherogenic process demonstrating lesions and plaques on the inner surfaces of the endothelial walls followed by invasion of VSM cells which become transformed phenotypes [4,16,17,43,45].…”
Section: What Happens If the Inflammatory Process Is Not Curtailed Ormentioning
confidence: 87%
See 4 more Smart Citations
“…These factors will sustain and perpetuate the atherogenic process forming, eventually, fibrous tissue and further enlargement of the lesion, which will overlie a core of lipid resulting in plaques and necrotic tissue. Using rabbits and rats, we have demonstrated that feeding the animals diets low in Mg (similar to the levels found in American diets) results in all of the hallmarks of atherosclerosis, i.e., inflammation followed by release of hydrolytic enzymes, release of cytokines, release of chemokines and growth factors involved in the early stages of the atherogenic process demonstrating lesions and plaques on the inner surfaces of the endothelial walls followed by invasion of VSM cells which become transformed phenotypes [4,16,17,43,45].…”
Section: What Happens If the Inflammatory Process Is Not Curtailed Ormentioning
confidence: 87%
“…It has been shown by our group [4,25,43,51] and others [52][53][54] that ceramides, in increased levels, found in the atherogenic process[mixed in plaques; unpublished findings ], at least in rabbits, and stimulated in MgD states could be important causal and initiating agents [16,17].…”
Section: Causative Events and Pathways Leading To Inflammationatherogmentioning
confidence: 95%
See 3 more Smart Citations